Why do children pay more attention to grammatical morphemes at the ends of sentences?. Issue 3 (25th October 2017) - SUNDARA, Megha
Abstract: Children pay more attention to the beginnings and ends of sentences rather than the middle. In natural speech, ends of sentences are prosodically and segmentally enhanced; they are also privileged by sensory and recall advantages. We contrasted whether acoustic enhancement or sensory and recall-related advantages are necessary and sufficient for the salience of grammatical morphemes at the ends of sentences. We measured 22-month-olds' listening times to grammatical and ungrammatical sentences with third person singular -s. Crucially, by cross-splicing the speech stimuli, acoustic enhancement and sensory and recall advantages were fully crossed. Only children presented with the verb in sentence-final position, a position with sensory and recall advantages, distinguished between the grammatical and ungrammatical sentences. Thus, sensory and recall advantages alone were necessary and sufficient to make grammatical morphemes at ends of sentences salient. These general processing constraints privilege ends of sentences over middles, regardless of the acoustic enhancement.